2021
DOI: 10.1111/jpn.13655
|View full text |Cite
|
Sign up to set email alerts
|

Effect of poultry offal silage with or without betaine supplementation on growth performance, intestinal morphometry, spleen histomorphology of Nile tilapia (Oreochromis niloticus) fingerlings

Abstract: Fishmeal (FM) is the main protein source in fish feed. However, it is quite expensive due to its limited resources. Therefore, finding a dietary alternative to the FM to sustain fish production is crucial, and the current study was performed to assess the impact of poultry offal silage (POS) with or without betaine supplementation; as an effective and cheaper alternative to FM; on feed efficiency, growth performance, spleen morphology and intestinal morphometry of Nile tilapia (Oreochromis niloticus) fingerlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
3
0
3
Order By: Relevance
“…Concisely, Hassaan et al (2021) concluded that Nile tilapia fed the mixture of digestive enzymes and LAB had improved intestinal morphometrical features. Further, Nile tilapia-fed betaine displayed improved histo-morphological features (Eissa et al, 2021).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Concisely, Hassaan et al (2021) concluded that Nile tilapia fed the mixture of digestive enzymes and LAB had improved intestinal morphometrical features. Further, Nile tilapia-fed betaine displayed improved histo-morphological features (Eissa et al, 2021).…”
Section: Discussionmentioning
confidence: 93%
“…The inclusion of betaine in aquafeed resulted in high feed intake and growth performance of several aquatic animals (Ghosh et al, 2019;Shi et al, 2021). In Nile tilapia, betaine supplementation enhanced the growth performance and utilization of plant-based feeds (Eissa et al, 2021;Ismail et al, 2020).…”
mentioning
confidence: 99%
“…En esta evaluación se utilizaron la BAL 1 (cerdo), como materia prima se utilizó residuos de del fileteo de C. obscurus o D. conceptione, sometidos a tres temperaturas de incubación (TA o 30 °C o 40 °C), Tabla 3, se observa la evaluación del pH y el % A, donde el valor de estabilidad se obtuvo en el día 10 con pH 4,29, pH 4,15 y pH 4,22 según la temperatura de incubación respectivamente (TA o 30°C o 40°), donde el pH de estabilidad fue estadísticamente diferente a los obtenido en los días (3, 15 y 30), y semejante para en el día 5 a TA y 30 °C, el proceso a TA presentó menos variaciones del pH que a 30°C y 40°C, todos los pH obtenidos están dentro de los valores reportados en la estabilidad y viabilidad de diferentes ensilados (pH menores a 4,6) según (Eissa et al, 2022;Ghosh et al, 2022;Martins et al, 2016;Safari et al, 2022;Zapata et al, 2015). Durante el proceso de fermentación el EB fue más estable a partir de día 5, incubados a 30 °C y TA; también a 40 °C presento aumento del pH posterior a día de estabilidad sugiriendo un inicio de degeneración anticipada, frente al día 15 para TA y 30 °C, los valores de estabilidad y viabilidad obtenidos con estas temperaturas de incubación son semejantes a las del ensilado reportados por (Ghosh et al, 2022), pero menores a los reportados en el ensilaje de pescado de (Guimarães et al, 2021).…”
Section: Evaluación Del Eb a Diferentes Temperaturas De Incubaciónunclassified
“…El EB es una alternativa de conservación mejorada (Safari et al, 2022), se caracterizan por prolongar la vida útil de la materia prima convirtiéndola en una alternativa para la alimentación animal (Fernández et al, 2017;Mohanty et al, 2020;Ziyaei & Hosseini, 2021). El ensilado biológico (EB) utiliza mayormente bacterias ácido lácticas (BAL) nativas, en un proceso de fermentación controlada y eficiente (Lezcano et al, 2015;Nag et al, 2022), utiliza subproductos del procesamiento de aves (Eissa et al, 2022), peces e hidrobiológicos (vísceras, cabezas, colas) es considerado un proceso de hidrólisis controlada (Okoye et al, 2023), que mejora el valor nutritivo de la materia prima utilizada (Palkar, 2018;Ziyaei & Hosseini, 2021), aportan nutrientes esenciales y funcionales (Sun et al, 2023). El EB agregado a las dietas mejora la salud intestinal con propiedades funcionales, BAL productoras de feruloil esterasa, antimicrobiano, ácido láctico con alto potencial antioxidante (Guo et al, 2023), buscando BAL de alto rendimiento que mejore la nutrición animal (Okoye et al, 2023;Sajib et al, 2022), de pollos y cerdos (Castillo et al, 2019;Fernández, 2021; P. P. García et al, 2020;Shabani et al, 2019), además se pude utilizar y combinar como materia prima vegetal (Costa et al, 2024), oleaginosos, algas, pescado y otras materias orgánicas (Castillo-Mercado et al, 2020;Rathod & Kairam, 2018).El EB es una buena alternativa de bioconservación (Nag et al, 2022).…”
Section: Introductionunclassified
“…By 2050, the global population is estimated to reach approximately 9.7 billion persons (Abdelatty et al 2018). To help meet the nutritional demands of the growing global population, substantial quantities of conventional poultry feedstuffs, such as corn and soybeans, are being reallocated from animal production to human nutrition purposes (Eissa et al 2021). With this shift, there has been an increased competition between livestock and poultry industries and human populations for these feedstuffs which has resulted in their limited availability and increased costs (Bakeer et al 2021).…”
Section: Introductionmentioning
confidence: 99%